Spatial Model For Planning Sustainable Leadership Development Through Leadership Skills: A Case Study In Kabupaten Bintan (International Journal of Environmental Sciences, 2025)
Spatial modelling provides valuable perspectives for analyzing and planning long-term leadership development, particularly in decentralized and tourism-dependent communities. This study offers a spatial model for assessing leadership abilities in Indonesia's KabupatenBintan, a region characterized by a variety of environmental and socioeconomic circumstances. Even though community-based leadership is becoming more and more important in spatial development, there are still few empirical studies that combine leadership and spatial analytics. Five fundamental leadership qualities including communication skills, critical thinking, moral & ethical skills, leadership skills and community involvement were evaluated quantitatively by distributing structured questionnaires to 300 respondents in seven villages. Relative Importance Index (RII) analysis was used to rank competencies, while GIS-based spatial mapping identified geographic differential in leadership capacities. Findings showed that moral and ethical skills were the highest attributes as evidenced by the top three indicators having RII values greater than 0.89 which were respect for the values of other cultures (RII = 0.907), does not criticize one's own ethics and culture (RII = 0.895) and respects the rights of others (RII = 0.894). Spatially, urban and coastal locations like Bintan Timur and TelukSebong had stronger leadership performance, whilst isolated areas like TelukBintan displayed lower scores on the majority of variables. These differences show how institutional support and infrastructure accessibility affect leadership preparedness. This research helps localize SDGs 11 (Sustainable Cities and Communities) and 13 (Climate Action) by offering useful insights for planners and policymakers to prioritize region-specific measures.